Cyst of canal of Nuck-a rare clinical entity: case series and review of literature - Albal, Manisha; Bansod, Prasad Y.; Singh, Pratik; Dhole, Rahul (International Surgery Journal, 2021)
A small evagination of parietal peritoneum forms the canal of Nuck. By the first year of life this extension condenses into a fibrous cord. Cyst of canal of Nuck is a rare developmental anomaly. The inguinal canal is traversed by the spermatic cord in male and the round ligament of uterus in female. The processus vaginalis accompanies the round ligament through the inguinal canal through into the labium majus. This evagination of parietal peritoneum forms the canal of Nuck in the female. These cases are rarely seen in surgical practice. In this case series we described three clinical scenario of canal of Nuck and their management.